Islamic Religious Education in Public Universities: Responding to Contemporary Challenges - Khoerudin, Koko; Fadilah, R. Muhamad Yasin; Setiawan, Edi (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
This research aims to explore the management of Islamic Religious Education (PAI) in public universities, particularly at Advanced Indonesia University (UIMA), and to identify efforts to enhance its effectiveness in instilling moral and religious values relevant to current developments. The research adopts a qualitative approach with a descriptive method to provide a systematic overview of the factors influencing the success of PAI, including both teaching aspects and supporting infrastructure. The study identified several challenges, including variations in religious education models, the need to integrate the inclusive spirit of Islamic teachings, educator professionalism, and the limitations in religious infrastructure. Proposed solutions include strengthening the curriculum based on the fundamental values of the Qur'an and Sunnah, alongside a holistic approach that not only focuses on academics but also on character and ethics formation. Additionally, the development of facilities, such as mosques, is expected to support increased religious activities. The conclusion of this research is that the management of PAI at public universities, like UIMA, requires an integrated approach that blends academic knowledge with support from various stakeholders to foster a competitive and character-building Islamic education. Penelitian ini bertujuan untuk mengeksplorasi tantangan dalam pengelolaan Pendidikan Agama Islam (PAI) di perguruan tinggi umum, khususnya di Universitas Indonesia Maju (UIMA), serta upaya untuk meningkatkan efektivitasnya dalam menanamkan nilai-nilai moral dan agama yang relevan dengan perkembangan zaman. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif untuk menyusun gambaran sistematis mengenai faktor-faktor yang memengaruhi keberhasilan PAI, baik dari aspek pengajaran maupun infrastruktur pendukung. Hasil penelitian mengidentifikasi berbagai tantangan, termasuk model pengembangan pendidikan agama yang berbeda, pentingnya integrasi semangat inklusivitas ajaran Islam, profesionalisme pendidik, dan keterbatasan sarana prasarana keagamaan. Solusi yang diusulkan mencakup penguatan kurikulum dengan dasar nilai-nilai fundamental Al-Qur’an dan as-Sunnah, serta adopsi pendekatan holistik yang tidak hanya mencakup aspek akademis tetapi juga pembentukan karakter dan etika mahasiswa. Selain itu, pengembangan sarana seperti masjid diharapkan dapat mendukung peningkatan aktivitas keagamaan. Kesimpulan dari penelitian ini adalah bahwa pengelolaan PAI di perguruan tinggi umum, seperti UIMA, tidak hanya membutuhkan pendekatan yang terintegrasi dengan ilmu pengetahuan umum, tetapi juga dukungan dari berbagai pihak untuk mencapai pendidikan Islam yang berdaya saing dan berorientasi pada pembentukan karakter Islami.